2020–2021 Vegetable Production Handbook: Chapter 5. Ethnic Vegetable Production - Guodong Liu; Christian F. Miller; Bonnie Wells; Yuncong Li; Peter Dittmar; Qingren Wang (EDIS)
The objectives of this publication are to (1) provide various names of some ethnic/Asian vegetable crops with EDIS publications available to readers; (2) list related chapters in this handbook, which provide recommendations for crops close to these ethnic vegetables grown in Florida; and (3) list EDIS publications currently available for these crops.